A Study on Parents’ Perception of School Program (Pemenuhan Gizi dan Kesehatan) in Improving Students’ Academic Achievement In Selected Primary Schools - Siti Salmah; Angela Syafriani (CV. Creative Tugu Pena, 2025)
The aim of this study was to examine parents’ perceptions of the school program (pemenuhan gizi dan kesehatan) which is a program introduced by the Ministry of Education of Indonesia as part of its effort to enhance students’ academic achievement. This phenomenological qualitative study was conducted among six parents of primary school children in the area Northen Sumatra. These parents were divided into three categories; non-working mothers, working mothers and working fathers. Individual interviews were carried out to collect the data in the study. Results revealed that the parents agreed to and lauded the importance of parental support. However, the results indicated that the parents’ knowledge of the program differed and their perceptions varied. They faced similar challenges in supporting their children’s learning but developed different strategies to overcome them based on their different social backgrounds, genders and occupations.